KINERJA DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MELAKSANAKAN PROGRAM PENGURANGAN ANGKA PENGANGGURAN - Hanifah, Indri; Pratidina, Ginung; Seran, M.YGG (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2018)
The purpose of this research is to know the performance of Dinas Tenaga. Work andTransmigration in implementing the unemployment reduction program of Bogor City. Thetheory used to measure the performance of Disnakertrans in implementing unemploymentreduction program of Bogor City is the theory put forward by Dwiyanto (in Pasolong 2007)on bureaucratic performance measures. This theory says that there are 6 (six) indicatorssuch as productivity, quality, responsiveness, service, accountability, and responsibilitas.The method in this research using descriptive qualitative research method. Whilethe data analysis technique used is using Interactive model developed by Miles andHuberman (in Sugiyono 2010), which includes data reduction, display data, and conclusiondrawing / verivication data collection techniques used are interviews, direct observationand documentation. The informants that the researchers took were two types ofinformants, firstly some employees of Disnakertrans were considered to be involved in theprogram of reduction of unemployment rate and second was 2 participants who hadattended the program.The results of research on the performance of the Department of Manpower andTransmigration in implementing the program of reduction of unemployment rate in thecity of Bogor is good. Because so far, the Manpower has done everything possible inimplementing the existing program despite some obstacles. With this result, it is expectedthat the Manpower and Transmigration Office will be able to overcome the obstaclesexperienced and the better performance and reduce the unemployment rate in Bogor citytoday.Keywords: Performance, Bureaucratic Performance, Unemployment Program